Patients’ satisfaction towards eye care services at tertiary eye hospital in western part of Nepal - Thapa, Saraswati Khadka; Thapa, Hari Bahadur; Upadhyay, Hari Prasad (Journal of Chitwan Medical College, 2021)
Background: Patient satisfaction is the level to which the patients’ experience that their needs and expectations are being met by the service provided. The aim of the study was to measure and improve the quality of eye care services at Lumbini Eye Institute and Research center (LEIRC)/Shree Rana Ambika Shah Eye Hospital (SRASEH) both pediatric and adult groups. Methods: A cross sectional study with descriptive analysis was done from November 2018 to April 2019 at LEIRC, Bhairahawa Nepal. Five hundred seventeen (517) patients were enrolled by systematic random sampling, segregating 201- In patients, 205 – adult and elder patients and 111 pediatric patients. Interview was taken from the patients using the questionnaire which was already used in Arvind Eye Care System, India after validating in our context. Data was entered and analyzed using IBM SPSS -20 version. Results: Among 517 respondents Female (54%) respondents were more than male. Overall patient satisfaction was almost ninety-eight percent were satisfied. Similarly, more than eighty (83.94) percent felt the reasonable cost in service charge and almost sixty five percent respond the reasonable waiting time. Ninety percent patients expressed their interest to recommend their friends or relatives to the hospital. Conclusions: Majority of the patients were satisfied with the overall services of the LEIRC. However, there is need to reduce longer waiting time of the patients.